(untitled) (Journal of Population and Development, 2023)
This research delves into the transformative realm of Black Aesthetics as a profound and resilient cultural resistance strategy employed by African-Americans. In a historical context marked by the degradation of the genuine image of African-Americans through Western perspectives, Black Aesthetics emerges as a dynamic force challenging stereotypes and reclaiming agency over cultural narratives. The study explores the foundational influences of key socio-political movements, namely the Harlem Renaissance, the Black Power Movement, and the Civil Rights Movement, in shaping and catalyzing the development of Black Aesthetics. During the 1920s, the Harlem Renaissance served as a crucible for cultural revitalization amid the multifaceted struggles faced by African-Americans. Fueled by a desire to break free from racial stereotypes, this movement laid the groundwork for the emergence of Black Aesthetics as a tool for empowerment and self-expression. The subsequent impact of the Black Power Movement and the Civil Rights Movement on Black Aesthetics is examined, revealing how these movements contested prevailing Western perspectives and sought to redefine the narrative surrounding African-Americans. The Black Power Movement, emphasizing self-determination and autonomy, stood in stark contrast to the assimilations goals of the Civil Rights Movement, collectively contributing to the nuanced evolution of Black Aesthetics. Through an interdisciplinary lens, this research navigates the intersection of art, ideas, and socio-political dynamics, elucidating how Black Aesthetics serves as a cultural resistance mechanism. It explores the multifaceted dimensions of this resistance, including the creation of alternative narratives, the celebration of cultural identity, and the reclamation of dignity. Ultimately, this research contributes to a comprehensive understanding of Black Aesthetics as a transformative force in cultural resistance, shedding light on its historical roots, its evolution through significant movements, and its enduring impact on reshaping the narrative of African-American identity.